2019
DOI: 10.19102/icrm.2019.100802
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation Patterns in Patients with Atrial Fibrillation Following Percutaneous Coronary Intervention in an Academic Center

Abstract: A common dilemma facing physicians treating patients with atrial fibrillation (AF) who have undergone percutaneous coronary intervention (PCI) is the management of oral anticoagulation (OAC) therapy, because there is also an indication for dual antiplatelet therapy in these patients. The purpose of this study was therefore to evaluate anticoagulation patterns in this patient population in an attempt to identify patterns of risk factors that may influence OAC prescribing habits. This retrospective study entaile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Not uncommonly, physicians have used a fear of more elderly patients falling and suffering a head or other major injury as a reason to avoid anticoagulation. While we have no way of knowing from the Rusia et al 1 report whether this was the case in their surveyed institutions, there is literature-reported data to indicate that this concern is excessive. In 2012, Donze et al examined 515 consecutive adult medical patients discharged on an OAC.…”
mentioning
confidence: 79%
See 4 more Smart Citations
“…Not uncommonly, physicians have used a fear of more elderly patients falling and suffering a head or other major injury as a reason to avoid anticoagulation. While we have no way of knowing from the Rusia et al 1 report whether this was the case in their surveyed institutions, there is literature-reported data to indicate that this concern is excessive. In 2012, Donze et al examined 515 consecutive adult medical patients discharged on an OAC.…”
mentioning
confidence: 79%
“…Simply put, the oldest patients with AF are those who have the highest risk of stroke and the most to gain from anticoagulation." Second, and disturbing rather than encouraging, Rusia et al 1 found no statistical association between discharge on an OAC and CHA 2 DS 2 -VASc score, with a worrisome trend occurring in the opposite direction. A higher CHA 2 DS 2 -VASc score indicates a greater risk for thromboembolism in AF and should be associated with a higher use of OACs.…”
mentioning
confidence: 96%
See 3 more Smart Citations